Neurodegenerative substrate of behavioral changes in Alzheimer's disease: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Ringman, John M; Pawar, Sanjay; Montoya, Lucy; Ge, Xinting; Qiao, Yuchuan; Shi, Yonggang
Abstract: Background: Neuropsychiatric symptoms (NPS) are common in Alzheimer's disease (AD) and, with advancing disease, are a major cause of disability and the principal cause of institutionalization. With the advent of tau imaging with PET, we can directly interrogate the neurodegenerative changes associated with behavioral changes in AD. Method: We performed flortaucipir PET scans in persons carrying autosomal dominant AD (ADAD) mutations and with late‐onset AD (LOAD). The Neuropsychiatric Inventory (NPI) was administered to knowledgeable study partners and the frequency x severity scores calculated for each behavioral domain. All underwent scans with flortaucipir using 110‐minute uptake time and 30‐minute dynamic scanning. PET scans were first normalized to T1 space and then corrected for partial volume effects using Mueller‐Gaertner approach. SUVRs for PET scan were calculated using the whole cerebellum grey matter as a reference. Regional average SUVRs were finally obtained for each ROI mapped from the Desikan‐Killiany Atlas. NPI scores for each domain were correlated with SUVRs using Pearson's correlations. Result: We included 24 participants (53% male, mean MMSE = 21, CDR = 0.8, CDR SOB = 4.6) with ADAD mutations (mean age = 38) and 6 participants with LOAD (mean age = 60). Strong (p's < 0.01) correlations were found for affective behaviors (apathy>depression>anxiety) and tau SUVRs in the anterior cingulate gyrus and medial orbitofrontal lobe. The highest correlations were found between apathy and tau signal in these areas (r = 0.67, p < 0.001). Conclusion: Changes in affect correlated strongly with tau pathology in the medial and orbital frontal lobes. This is consistent with previous studies implicating a role or these areas in apathy and depression. These findings enhance our understanding of the pathology underlying affective symptoms in AD and suggest a role of tau PET in identifying those at the greatest risk for these debilitating symptoms.